Seed Germination and Reproductive Capacity of Lasiurus sindicus Henr - Bishnoi, S; Gautam, D D; Kumar, K (Annals of Arid Zone, 2016)
Germination of L. sindicccs seed is hypogeal type. Natural plant population have three categories of seed : large, medium and small. The optimum temperature for germination is 320 f 1-1. The average percentage germination is 67 f 5.56. The average seed output is 9471 plant-1Â and it varied with the size of the plant. The reproductive capacity is 6345.57